The Influence of Balinese Dancing on Children’s Self Confidence in Denpasar, Bali - Ni Made Ari Sukmandari; Komang Yogi Triana; Putu Ari Sukriyanti (Gema Lingkungan Kesehatan, 2026)
School-aged children tend to prefer physical and social activities. This period is the right time to develop oneself in areas such as physical, cognitive, language, social, emotional, spiritual, self-concept, discipline, and independence. Self-confidence is a personality trait that can be characterized by the ability to interact with friends and family. This research aims to determine the effect of Balinese dancing activities on the self-confidence of school-aged children at the Denpasar Dance Studio. This research uses a quasi-experimental design, particularly the pre-test-post-test control group design. Self-confidence measurements for school-age children were carried out twice a week for one month, while the control group was beginner musicians who had never performed. The sampling technique used in sample selection was purposive sampling with inclusion and exclusion criteria. The difference in pre-test and post-test results using the Wilcoxon signed rank test in the intervention group, with a p-value of 0.000, signifies that Balinese dancing activities influence self-confidence in school-aged children. Meanwhile, in the control group, the p-value was 0.993, meaning that beginner Balinese music activities did not affect the self-confidence of school-aged children. The Mann-Whitney test found a p-value of 0.005, indicating a difference in the self-confidence of school-aged children in the intervention and control groups. It is hoped that this research will provide input for parents to provide physical activity in the form of Balinese dancing to school-aged children to increase their self-confidence.